Cirebon City Police Residential Sat Efforts to Use CCTV to Reveal Criminal Acts of Theft - Safrizal Wiratama, Fakhri (Indonesian Journal of Police Studies, 2024)
The title is backed by the high number of motor vehicle theft that occurred in the city of Cirebon in the last five years and the associated benefits are installed Closed Circuit Television (CCTV) to find the identity of suspects and evidence when carrying out its action. This research is done with a qualitative approach and uses a type of field research as well as a juridical approach to empirical. The focus of research in this is the use of CCTV in the process of disclosure of Curanmor criminal act conducted in the city of Cirebon Polres. The result of this research is in performing the action suspect to observe according to the target is sought, lack of care in every environment, especially if there is no CCTV in the house, and the lack of economic motivation that is the reason for suspects to commit crimes. In the use of CCTV investigation and criminal polres Cirebon City conduct observation of any electronic documents used as a tool of evidence in accordance with Article 5 paragraph 1 and 2 of Law No. 11 of 2008 on electronic information and transactions. The use of CCTV is given some supporting factors such as the existence of clear legal certainty so investigators hesitate to use this proof tool, the law enforcement factor that has the expertise in identifying the recording on CCTV, but there is a barrier that is a factor of infrastructure that does not support. Lack of quality of CCTV recordings is becoming an inhibitor of identification process. But the level of public awareness in installing CCTV in consciousness around the house or shops has begun to exist. Based on the results of the research, the authors give advice to include investigators and new analytical teams in the handling of criminal acts, updates of effective supporting features and manufacture of SOP use of CCTV, integrated CCTV procurement, and socialization of CCTV installation in public places to make the perpetrators undo their intention to commit crimes, especially the theft of motor vehicles.